IMPLEMENTING THE HACCP CONCEPT IN NIGERIAN TONGUE SOLE FISH (Cynoglossus browni) FILLETS AND MINCE PRODUCTION IN A FISH PROCESSING PLANT FOR EXPORT - Fajana, Oluwafemi Paul; Mekuleyi, Gabriel (International Journal of Food Sciences, 2019)
Purpose: This study was carried out in the Fish processing plant of Olokun Pisces Limited from June - November, 2018 with the primary focus on implementing Hazard Analysis Critical Control Point (HACCP) concept as a tool to ensure safety of food products. Sole fish Fillets and Mince were produced from mechanized raw processing of Nigerian tongue Sole fish (Cynoglossus browni) using the knowledge of HACCP application. Methods: The Processing Plant is owned by Olokun Pisces Limited (Lat N 60 28Ë¡ 24Ë¡Ë¡, Long E 30 22Ë¡ 50Ë¡Ë¡), a Private Fishing Company located in Otto, Lagos, Nigeria. The Company has over thirty trawlers licensed by the Federal Department of Fisheries (FDF) to fish in Nigerian Coastal waters which falls within Eastern Central Atlantic FAO Area 34. The Nigerian coastal line has eight states it shares borders with. They are Lagos, Ogun, Ondo, Rivers, Delta, Akwa Ibom, Bayelsa and Cross River States. A trawler voyage of about fifty (50) days to and fro covers the coastal waters including the eight coastal states. The study was carried out from June - November, 2018. On board frozen Cynoglossus browni is being received in bags (20kg net weight) from the trawler vessels upon arrival and stored in the cold room (with a temperature of -200C) prior to processing. Cynoglossus browni being a demersal species was caught by method of bottom trawling. Results: The HACCP concept focused on the safety of sole fish fillets and mince through a systematic and scientific approach to hazard identification, assessment and control. Preventive and control measures in dealing with identified hazards helps to eliminate or reduce hazards to acceptable levels. Pre-requisite programs consolidate the effectiveness of the HACCP in achieving safety of food products. The verification exercise confirmed that the HACCP concept implemented in the processing of Sole fish fillets and mince was adhered to and the products are safe, fit for consumption and ready for export. Unique contribution to theory, practice and policy:To achieve safety of food products requires the joint effort of the HACCP team. Hence, adequate training of the team members on recent developments and changes in the food industry is very key to consistently improve efforts to always maintain the quality brand the product is known for.